The Design and Relevance of a Computerized Gamified Depression Therapy Program for Indigenous Māori Adolescents - Shepherd, Matthew; Fleming, Theresa; Lucassen, Mathijs; Stasiak, Karolina; Lambie, Ian; Merry, Sally N (JMIR Publications, 2015)
BackgroundDepression is a major health issue among Māori indigenous adolescents, yet there has been little investigation into the relevance or effectiveness of psychological treatments for them. Further, consumer views are critical for engagement and adherence to therapy. However, there is little research regarding indigenous communities' opinions about psychological interventions for depression. ObjectiveThe objective of this study was to conduct semistructured interviews with Māori (indigenous New Zealand) young people (taitamariki) and their families to find out their opinions of a prototype computerized cognitive behavioral therapy (cCBT) program called Smart, Positive, Active, Realistic, X-factor thoughts (SPARX), a free online computer game intended to help young persons with mild to moderate depression, feeling down, stress or anxiety. The program will teach them how to resolve their issues on their own using Cognitive Behavioural Therapy as psychotherapeutic approach. MethodsThere were seven focus groups on the subject of the design and cultural relevance of SPARX that were held, with a total of 26 participants (19 taitamarki, 7 parents/caregivers, all Māori). There were five of the groups that were with whānau (family groups) (n=14), one group was with Māori teenage mothers (n=4), and one group was with taitamariki (n=8). The general inductive approach was used to analyze focus group data. ResultsSPARX computerized therapy has good face validity and is seen as potentially effective and appealing for Māori people. Cultural relevance was viewed as being important for the engagement of Māori young people with SPARX. Whānau are important for young peoples' well-being. Participants generated ideas for improving SPARX for Māori and for the inclusion of whānau in its delivery. ConclusionsSPARX computerized therapy had good face validity for indigenous young people and families. In general, Māori participants were positive about the SPARX prototype and considered it both appealing and applicable to them. The results of this study were used to refine SPARX prior to it being delivered to taitamariki and non-Māori young people. Trial RegistrationThe New Zealand Northern Y Regional Ethics Committee; http://ethics.health.govt.nz/home; NTY/09/003; (Archived by WebCite at http://www.webcitation/6VYgHXKaR).